The Impact of Compensation and Job Satisfaction on Employee Performance: A Case Study of PT Bank XYZ (Persero) Tbk (Jurnal Bina Praja, 2024)
This research investigates the relationship between compensation and job satisfaction, as well as the influence of the latter on employee performance and productivity at PT Bank XYZ (Persero) Tbk, South Jakarta. By using SmartPLS 4.1.0.1 partial least square in analyzing the data from 135 respondents, it was found that compensation has a positive effect on employee performance but no influence on productivity, while job satisfaction has a positive effect on productivity but no influence on performance. The results showed that employee productivity has a significant influence on performance. Moreover, this study indicated that employee productivity mediates the relationship between job satisfaction and performance but fails to mediate the relationship between compensation and performance.
Keywords: Compensation; Job Satisfaction; Employee Productivity; Employee Performance; Financial Institutions